The effect of Jianpi Yangzheng Xiaozheng Decoction and its components on gastric cancer. (10th May 2019) - Wu, Jian; Zhang, Xing-Xing; Zou, Xi; Wang, Min; Wang, Hong-xing; Wang, Yao-hui; Li, Chang-yin; Zhao, Lin-gang; Chen, Min; Pei, Li-xia; Liu, Shen-Lin; Sun, Qing-Min
Abstract: Ethnopharmacological relevance: Jianpi Yangzheng Xiaozheng Decoction (JPYZXZ) is an empirical compound prescription based on the theory of traditional Chinese medicine. JPYZXZ, which is "Qi-invigorating, spleen-strengthening and stasis-removing, " can improve the quality of life of gastric cancer patients and prolong their survival; however, the exact mechanism underlying the antitumor effects of this compound is still not clear. Aim of the study: The aim of this study is to clearly define the effect of JPYZXZ and its components, Jianpi Yangzheng Decoction (JPYZ) and Xiao Zheng San Jie Decoction (XZSJ), on inhibiting the progression of gastric cancer. Materials and methods: The effect of JPYZXZ and its components on the motility of gastric cancer MGC-803 cells was measured by MTT, adhesion, transwell assays and wound-healing assays. JPYZXZ, JPYZ and XZSJ were administered to 615 mice with gastric cancer xenografts, and their effect on the inhibition of subcutaneous transplantation was analyzed. THP-1 monocyte cells were used to establish tumor-associated macrophage (TAM) models. The polarized state of the TAMs was detected by Flow Cytometry, ELISA and Immunohistochemistry. The mRNA and protein expression of tumor epithelial-mesenchymal transition (EMT) and TAM-related genes was determined by Real-time PCR and Western Blot, respectively. Results: We determined that both JPYZXZ and its components inhibited the progress of gastric cancer in vitro, and JPYZXZ was clearly more effective than JPYZ or XZSJ. The in vivo results demonstrated that the JPYZXZ and XZSJ group exhibited a significant decrease in the tumor weight compared to the control group. Further analysis indicated that JPYZXZ was more active than JPYZ or XZSJ in inhibiting the gastric cancer EMT transformation both in vivo and in vitro . However, JPYZ was more effective compared with JPYZXZ for inducing the phenotypic change in macrophages from M2 to M1. Conclusions: Our results demonstrate that both JPYZXZ and its components prevent the progress of gastric cancer. JPYZXZ inhibits the gastric cancer EMT more effectively than JPYZ and XZSJ, but JPYZ primarily works to regulate the phenotypic change in macrophages from M2 to M1. Graphical abstract: fx1